Os "cassacos" migrantes de Tamboara-PR : a mobilidade forçada e as resistências no processo de produção do espaço geográfico de Jardim-CE - Ribeiro, Vitor Hugo (2016)
Nowadays, the studies concerning to the populational movement runs through several geographical analysis scales highlighting its contradictions and conflicts as reflections of the globalization era. Globalization has conditioned the emergence of a class of workers unskilled in different branches of economic activities, being deterritorialized, precarious and dispossessed of their means of production. Such workers seek through forced mobility, better life and work conditions. This context reflects the current situation of relative labour force, especially related to young adults coming from the north-eastern region, linked to the sugarcane industry in Brazil. The absence of opportunities in certain Brazilian regions consubstantiated the neglect of local politicians have been hindering population retaining young adults in their home environment. This research has identified a class of Northeastern rural workers who migrates temporarily or permanently, to the Paranaense Northwest to join in cutting sugarcane or cassava. In this manner, the objective of this thesis is to investigate the Northeastern labor force in the Paranaense Northwest and its effects on the production of the geographic area of the municipality of Tamboara-PR. It also signals the municipality of Jardim-CE, city of origin of many immigrants from Tamboara to propose new economic activities guided by the alternative economy and the social and solidarity economy as eradication of forced mobility possibilities to paranaenses sugarcane fields. Such activities consist of population restraint devices and counter-hegemonic resistance face of globalization and the hegemonic globalization of social organization.